2021
DOI: 10.22146/rpcpe.70027
|View full text |Cite
|
Sign up to set email alerts
|

Management of Thirst in Hemodialysis Patients in Primary Services

Abstract: The incidence and prevalence of chronic kidney disease (CKD) has increased worldwide and in Indonesia. There were about 53,940 people with stage 5 CKD based on data from the Indonesian Renal Registry (IRR) in 2018. Incidence crude rate is 251 per million population and prevalence crude rate is 499 per million population for the entire population1. The prevalence of CKD has almost doubled in 5 years, from 2‰ in 2013 to 3.8‰ in 2018. Hemodialysis (HD) is a renal replacement therapy modality that is in great dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our findings also demonstrated a significant inverse relationship between TD and QOL. A study on patients receiving hemodialysis reported that fluid restriction caused these patients problems such as thirst, guilt, distress, and anxiety, while their constant exposure to thirst caused them fatigue and reduced their QOL 26 . Dryness of the mouth due to fluid restriction has a direct relationship with thirst and increases the risk of weight gain and orodental problems such as bacterial and fungal infections, candidiasis, dental caries, and periodontal diseases 94 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also demonstrated a significant inverse relationship between TD and QOL. A study on patients receiving hemodialysis reported that fluid restriction caused these patients problems such as thirst, guilt, distress, and anxiety, while their constant exposure to thirst caused them fatigue and reduced their QOL 26 . Dryness of the mouth due to fluid restriction has a direct relationship with thirst and increases the risk of weight gain and orodental problems such as bacterial and fungal infections, candidiasis, dental caries, and periodontal diseases 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, increased desire for salt intake which is associated with TD. TD can also lead to dryness in the mouth, reduced energy, and fatigue 25 , 26 . These complications may interact with each other, leading to a harmful cycle of negative physical and mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%